2021
DOI: 10.21037/atm-21-5367
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific nomogram models to predict the prognosis of male and female lung adenocarcinoma patients: a population-based analysis

Abstract: Background: Epidemiological and clinical prognosis differences between male and female lung adenocarcinoma (LUAD) patients have been frequently reported. To improve prognosis determinations, gender-specific nomogram models should be developed and validated to predict the prognosis of patients with LUAD. Methods: Using the Surveillance, Epidemiology, and End Results (SEER) database, LUAD patients diagnosed between 2010 and 2015 were used as SEER training and internal validation testing sets. Patients in Tianjin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
0
8
0
3
Order By: Relevance
“…Some clinical factors, such as gender, age, histological subtype and surgery, are related to survival of metastatic lung AD. [ 8 , 9 ] However, these elements are in ignorance of the location and quantity of organ metastatic sites. Approximately 57% of lung AD have advanced to metastatic diseases, and the prognosis of patients is adversely affected by organ metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical factors, such as gender, age, histological subtype and surgery, are related to survival of metastatic lung AD. [ 8 , 9 ] However, these elements are in ignorance of the location and quantity of organ metastatic sites. Approximately 57% of lung AD have advanced to metastatic diseases, and the prognosis of patients is adversely affected by organ metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that marital status was a protective factor for survival among patients with lung cancer [ 55 , 56 ]. The married patients in our study included married couples and those living with domestic partners, and singles were defined as single, widowed, divorced, and separated patients, which was a more detailed definition than previous studies [ 56 , 57 ]. We highlighted the potentially significant social impact of marital status on the survival of LUAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…40 (1) 18149 (72) 25170 ( 100) 9273 ( 37) 13072 (52) 4505 ( 18) 6576 (26) 1483 ( 6) 2825 (11) 373 ( 1 40) 1470 (56) 514 ( 19) 732 (28) 141 ( 5) 308 ( 12 39) 9473 (54) 3325 ( 19) 4775 (27) 1095 ( 6) 2110 ( 12 34) 6609 (48) 2195 ( 16) 3266 (24) 686 ( 5) 1328 (10) 175 ( 1 52) 7358 (69) 2864 ( 27) 4075 (38) 944 ( 9) 1792 ( 17) 230 (2) T1 7278 (74) 9892 ( 100) 3628 ( 37) 5219 (53) 1731 ( 17) 2561 (26) 548 ( 6) 1098 (11) 149 (2) T2 3226 ( 60) 5392 ( 100) 1368 ( 25) 2065 (38) 619 ( 11) 909 (17) 190 ( 4) 364 (7) 46 (1) T3 2499 ( 48) 5154 ( 100) 829 ( 16) 1433 (28) 303 ( …”
Section: Discussionunclassified
“…8 EGFR is the main driver gene in Asian patients, mostly in non-smoking, female, adenocarcinoma patients. 9 The discovery of EGFR tyrosine kinase inhibitor (EGFR-TKI) has revolutionized the traditional treatment of advanced NSCLC. 10 The effect achieved by chemotherapy alone is not significant in clinical treatment, while EGFR-TKI targeted therapy can effectively control tumor progression in the initial EGFR-sensitive advanced lung adenocarcinoma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8 EGFR is the main driver gene in Asian patients, mostly in non-smoking, female, adenocarcinoma patients. 9 The discovery of EGFR tyrosine kinase inhibitor (EGFR-TKI) has revolutionized the traditional treatment of advanced NSCLC. 10…”
Section: Introductionmentioning
confidence: 99%